THE EFFECTIVENESS OF LONG-TERM AZITHROMYCIN USING IN NON-SURGICAL THERAPY OF GENERALIZED CHRONIC PERIODONTITIS - Nepokupna-Slobodyanyuk, Т.S. (World of Medicine and Biology, 2014)
The study examines the effectiveness of long term azithromycin in combination with non-surgical periodontal therapy on clinical parameters and IL-1β, AST, ALT concentration levels in periodontal pockets over 360±5 days in patients with generalized chronic periodontitis (CP). Forty patients with generalized chronic periodontitis I, II and III levels of severity were included in this randomized, placebo-controlled, parallel-arm study. They were randomly assigned to azithromycin or placebo groups (500 mg once daily for 7 days, then 500 mg once a week for 12 weeks) of 20 people after initial periodontal treatment and sanation measures. Periodontal clinical parameters (PPD, BoP, CAL, teeth pathological mobility, PMA, hygiene indexes, calculus scores) and IL-1β, AST, ALT concentrations were evaluated before treatment and after 14±3, 30±5, 90±5, 180±5 and 360±5 days. The material for the study of IL-1β, ALT and AST were sample of periodontal pockets content from 1-2 same teeth received with paper pins. Determination of ALT, AST was performed by kinetic photometric (dinitrofenilhidrazyn) method. Determination of ІЛ-1β was performed by solid-phase sandwich enzyme-linked immunosorbent assay (ELISA) method. The long term adjuvant azithromycin provides clinical benefit in 80% of patients with generalized CP I-III levels of severity within 360±5 days with satisfactory tolerability, as confirmed significant decrease in IL-1β, AST, ALT in periodontal pockets.
Keywords: chronic generalized periodontitis; azithromycin; interleukin-1 beta